Peace Profile: David Davies, of Llandinam. (2nd January 2023) - Morgan, W. John
Abstract : David Davies, of Llandinam (1880–1944) was undoubtedly the most influential person in the peace movement in Wales during the first half of the 20 th century. The grandson of a prominent Welsh industrialist and businessman, also David Davies, he inherited great wealth, from a family of preeminent social standing in Montgomeryshire, his county of birth. This permitted Davies a philanthropy stimulated by idealist beliefs about how international relations should be conducted, given the terrible experience of the First World War. The article provides a profile of the man, his philanthropy, and his idealist philosophy of peace as expressed in his own words, with an assessment of Davies' influence on the peace movement in Wales, and beyond.